No Difference in Mood and Quality of Life in DHEA-S Deficient Adults with Addison’s Disease vs. Type 2 Diabetes Patients with Normal DHEA-S Levels: Implications for Management of These Conditions - Heald, Adrian H.; Walther, Andreas; Davis, Julian R. E.; Moreno, Gabriela Y. C.; Kane, John; Livingston, Mark; Fowler, Helen L. (Frontiers in Psychology, 2017)
Patients with Addison’s disease have relatively high rates of depression and anxiety symptoms compared with population-based reference samples. Addison’s disease results in deficiency of dehydroepiandrosterone (DHEA) and DHEA-sulphate (DHEA-S). There is considerable debate about the specific effects of DHEA deficiency on energy level and mood. We measured emotional well-being in 16 patients with Addison's disease and a group of 16 hospital attendees with type 2 diabetes. Participants completed the General Health Questionnaire-28 (GHQ-28), the Hospital Anxiety and Depression Scale (HADS), the World Health Organization’s quality of life assessment (WHOQOL-BREF) and the Holmes-Rahe life event scale. DHEA-S was low in Addison’s patients (Addison’s men: 0.5±0.1 μmol/l [normal range: 2.1-10.8] compared with diabetes men: 3.2±1.2μmol/l; Addison’s women: 0.4±0.01 μmol/l [normal range: 1.0-11.5] compared with diabetes women: 2.2±0.71 μmol/l). Testosterone levels were similar in both groups studied. There were no differences in emotional well-being and quality of life between patients with Addison’s disease and Type 2 Diabetes Mellitus as measured by GHQ-28 (Addison’s: 22.4±2.6, Diabetes: 19.6±2.7), HADS Depression (Addison’s: 5.4±0.9, Diabetes: 4.5±1.4), HADS Anxiety and WHOQOL-BREF. There were no gender differences in affective symptomatology within the Addison’s group. Life event scores were above average in both groups (Addison’s: 195±39.6, Diabetes: 131±43.8), but not significant for difference between groups as was GHQ-28 total score. Both groups scored highly on the GHQ-28 and the life event scale, indicative of poorer health perceptions than the general population. This could be due to the chronicity of both disorders. We have not identified any specific effects of DHEA-S deficiency on mood or quality of life.